Optimizing Scanning in Youth Female Football: The Role of Verbal Instructions - Mirjam Hintermann; Michael Romann; Dennis Lüdin; Wolfgang Taube; Jörg Fuchslocher (Current Issues in Sport Science)
Introduction In dynamic sports like football, where game situations change rapidly, gathering information through visual exploration is essential for expert performance (Aksum et al., 2021; Pokolm et al., 2022). While the importance of visual exploration for subsequent action performance is well-documented in men’s football (Aksum et al., 2021; Jordet et al., 2020), recent research highlights its equally critical role in women’s football (Hintermann et al., 2024). Despite coaches acknowledge the importance of visual exploration training, they often lack knowledge about effective training and developing methods (Eldridge et al., 2022). Verbal instructions, such as ‘check your shoulder’ or ‘head up’, are commonly used to encourage scanning during practice sessions and games (Pulling et al., 2018), however, their specific impact on scanning behavior and subsequent performance remains unclear. Therefore, this study examines the immediate effects of verbal instructions on scanning behaviour and subsequent performance during 4v4 small-sided games (SSG) among elite youth female football players. Specifically, it addresses two research questions: 1) Do verbal instructions increase the number of scans performed before receiving the ball? 2) Do players improve their performance in response to verbal instructions fostering scanning behavior?